Corrosion behavior of API 5L X65 steel subject to plastic deformation - Oliveira, Mariana Cristina de [UNESP]; Figueredo, Rodrigo Monzon [UNESP]; Acciari, Heloisa Andrea [UNESP]; Codaro, Eduardo Norberto [UNESP] (Elsevier B.V., 2018)
The API 5L X65 steel is widely used as one of the most economical and safe ways of transporting oil and gas. The significant number of accidents caused by failures of pipelines is due to corrosion. Plastic deformation can modify the mechanical properties of these pipelines, so study the steel's corrosive behavior when deformed plastically is important to avoid failures. In this research, samples were taken from a region free of solder and plastically deformed from 0 to 2.5% in a tensile machine. The samples were analyzed by chemical and electro-chemical tests in NACE 177-A solution. It was concluded that the corrosion resistance was not affected by the different conditions of plastic deformation. (C) 2018 Brazilian Metallurgical, Materials and Mining Association. Published by Elsevier Editora Ltda. This is an open access article under the CC BY-NC-ND license.
Keywords: API 5L X65; Plastic deformation; Corrosion; Electrochemical